2022
DOI: 10.1186/s41606-022-00082-w
|View full text |Cite
|
Sign up to set email alerts
|

Lingering impacts on sleep following the Daylight Savings Time transition in the Project Baseline Health Study

Abstract: Background The “spring forward” change to Daylight Savings Time (DST) has been epidemiologically linked with numerous health and safety risks in the days following the transition, but direct measures of sleep are infrequently collected in free-living individuals. Methods The Project Baseline Health Study (PBHS), a prospective, multicenter, longitudinal representative U.S. cohort study that began in 2017 launched a Sleep Mission in March 2021 to cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These results suggest that the Spring transition is associated with reduced sleep duration. It is difficult to directly compare our results which look at sleep duration each day (from midnight to midnight), to studies that examine sleep each night (from noon to noon) 10, 12 . However, we found a loss of sleep greater than that seen in previous studies which have reported a 5-30 minute reduction in sleep duration on the night of the Spring clock change 10, 12 and a study reporting a 30 minute reduction on the Sunday of the change 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that the Spring transition is associated with reduced sleep duration. It is difficult to directly compare our results which look at sleep duration each day (from midnight to midnight), to studies that examine sleep each night (from noon to noon) 10, 12 . However, we found a loss of sleep greater than that seen in previous studies which have reported a 5-30 minute reduction in sleep duration on the night of the Spring clock change 10, 12 and a study reporting a 30 minute reduction on the Sunday of the change 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of the effects of DST transitions on sleep have relied on subjective self-report data 10, 11, 14, 15, 19, 20 , which may be affected by recall bias and have been shown to only moderately correspond to more objective measures of sleep, such as actigraphy 26 . Whilst some DST research has used actigraphy data, most of these studies have suffered from small sample sizes (n < 100) 13, 1618 , reducing their estimates’ precision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DST was originally designed and promoted for individuals with outdoor lifestyles by increasing their daylight exposure. In contemporary society, human spend most of their time indoors (on average 87% 1 ), where they may experience limited exposure to natural light and are particularly susceptible to the effects of DST transitions, which can disrupt circadian rhythms and impair sleep duration and quality 2 5 . These effects may persist for several days after the shift, or even longer 6 .…”
Section: Introductionmentioning
confidence: 99%